Sosialisasi Pentingnya Keamanan Data Digital Bagi Perempuan Penyandang Disabilitas Di Kota Makassar - Abdal, Nurul Mukhlisa; Shabrina Syntha Dewi; Ninik Rahayu Ashadi; Dwi Rezky Anandari; Syahrul; Labusab; Andi Zulfikar Yusuf (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
This community service activity focuses on raising awareness about the importance of digital security for women with disabilities in the city of Makassar. It addresses the following issues: 1) Some women with disabilities have experienced being victims of digital crime. 2) Lack of understanding about digital data security makes it difficult for them to identify fraud and protect their personal information on digital devices. 3) Limited knowledge on maintaining data security while using digital devices, resulting in a lack of strategies to stay vigilant against digital crime threats. The objective of this activity is to enhance the understanding of digital security among women with disabilities, enabling them to use digital devices correctly and safely. By doing so, we aim to empower women with disabilities to become less susceptible to digital crimes. This socialization initiative employs various methods such as lectures, discussions, tutorials, and demonstrations. These sessions focus on improving data security and prevention techniques, addressing the prevalent digital crimes occurring in today's world. The outcome of this community service activity is an increased understanding and awareness among participants regarding the evolving digital era and the need to be vigilant when using digital devices. Consequently, we anticipate participants to be capable of enhancing data security on their respective digital devices. Furthermore, this socialization effort also nurtures participants' interest and skills in promoting the use of digital technology to enhance digital data security for women with disabilities, particularly in the city of Makassar.